Ù…Ø´ÙƒÙ„Ø§Øª ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„ØµØ±ÙÙŠØ© Ù„Ø·Ù„Ø¨Ø© Ù‚Ø³Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠÙ‘Ø© Ø¨Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠÙ‘Ø© Ø§Ù„ØÙƒÙˆÙ…ÙŠÙ‘Ø© ÙÙˆÙ†ÙˆØ±ÙˆÙƒÙˆ - Mujib, Ahmad; Bashori, Ahmad (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2020)
The purpose of this study is to describe the learning of Qowaid Shorf on students majoring in Arabic Language Education at the State Islamic Institute of Ponorogo and the problems that cause the Qowaid Shorf learning objectives to not be achieved. The research method used is qualitative research with miles and huberman models. The results of the study include: 1) The implementation of learning qowaid on students majoring in Arabic Education at the State Islamic Institute of Ponorogo using inductive and deductive methods, 2) Problems encountered in learning qowaid on students majoring in Arabic Education at the Institute of Islamic Religion in the State of Ponorogo are levels knowledge and skills about Arabic that are owned by students before learning shorf vary, the assumptions that arise in the majority of students that shorf is a science that is difficult to master, lack of motivation, interest and encouragement in students in learning Arabic, lack of practice in terms of the rules learned, things These are very influential on the process and learning outcomes of Qowaid Shorf